Identifying and coping with the dilemmatic goals of university performance measurement systems in Finland - Lepistö, Lauri; Lepistö, Sinikka; Kallio, Kirsi-Mari; Kuoppakangas, Päivikki (Sage, 2025)
Performance measurement systems (PMSs) form an integral part of universities’ management processes, but their designs and applications have received criticism. As such systems are prevalent in universities, this study aimed to highlight the dilemmatic nature of university PMSs by illustrating their contradictory goals and discussing coping mechanisms to delineate the need for PMS development. The data used in this study were obtained from 23 interviews with administrative managers at 12 university departments of three universities in Finland. The data were analysed using a dilemma approach, which is considered useful for analysing problems that include difficult choices between opposing options. The analysis identified three dilemmas in the university PMSs: 1) measuring individual performance versus the quality of academic work, 2) rewarding good performance versus using scarce resources efficiently and 3) measuring performance in teaching versus research. This paper describes how the university departments have begun to deal with the identified dilemmas. It argues that by explicitly identifying the dilemmas revolving around PMSs, their interdependence can be observed, which affects coping with these dilemmas. The results of this study suggest that extending the role of PMSs from evaluating to incorporating different forms of rewards would help reconcile the observed dilemmas.